Do pandemics lead to rebellion? Policy responses to COVID-19, inequality, and protests in the USA - Francesco Iacoella; Patricia Justino; Bruno Martorano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper analyses how inequality across counties in the United States of America has shaped the impact of the COVID-19 pandemic on the incidence of protests. The empirical analysis combines weekly data between January and December 2020 on levels of COVID-19-related policy stringency and protest incidence at the county level with measures of county-level inequality at the start of the pandemic. The results show that more stringent measures to contain the pandemic were instrumental in driving the incidence of protests, but only in counties with high levels of inequality before the start of the pandemic, where grievances may have been initially stronger. Further analysis suggests that the impact of government responses to the COVID-19 pandemic is largely explained by changes in economic conditions (rise in unemployment and changes in economic activities and spending) in counties with the highest levels of inequality. Unequal counties with lower trust in political institutions but higher levels of social trust and civic engagement at the start of the pandemic are also more likely to experience more protests as a response to more stringent policies.
Keywords: I18; D63; D70; 330; COVID-19; lockdown; protests; inequality